Silicate, phosphate and carbonate mineral dissolution behaviour in the presence of organic acids: A review - Lazo, D.; Dyer, L.; Alorro, Richard (Elsevier, 2017)
Researchers in the field of geoscience have identified several effects on the stability of the surrounding minerals caused by naturally occurring solution species. Organic acids and their conjugate salts have been shown to provide significant influence on a wide range of minerals, generally increasing elemental mobility and aiding in solubilising the solid matrix. Their ability to complex elemental and molecular species, presents interesting opportunities in manipulating systems to achieve outcomes that are otherwise not thermodynamically favoured. Such properties form the basis of some analytical techniques such as the toxicity characteristic leaching procedure (TCLP) used in environmental assessment of waste product stability and the acidified ammonium oxalate (AAO) process used to selectively dissolve poorly crystalline iron oxide phases. These characteristics also present the opportunity for use of these species to aid in industrial dissolution of value-containing minerals (extractive metallurgy). Such an approach provides the basis for the current review. The literature has been reviewed to identify organic acids – particularly low molecular weight organic acids (LMWOAs) – that significantly aid dissolution of relevant minerals, trends in their behaviour and fundamental explanations for these observations. It is also of interest to find evidence that these acids may improve selectivity in a hydrometallurgical application. This review is limited to silicate, carbonate and phosphate minerals as they represent the information relevant to the ongoing research. Formic and acetic acids had the greatest impact on minerals composed of group I and II elements, while citric, oxalic, EDTA and salicylic acids represent the most promising options for transition metal and lanthanide-based minerals. The variation between the effect of the acids and a degree of the selective nature of their effect can be attributed to differences in the stability of the metal-ligand complex formed. pH plays a highly significant role, assisting the dissolution through, altering the dissociation of the acids, modifying the surface charge of the mineral, acid attack, maintaining the solubility of other dissolved ions and/or altering the mechanism involved. The crystal structure and secondary reactions occurring with other constituents in the mineral alter their amenability to dissolution in organic acids.